Synthesis, Solvatochromic Performance, pH Sensing, Dyeing Ability, and Antimicrobial Activity of Novel Hydrazone Dyestuffs. (5th February 2019) - Khattab, Tawfik A.; Allam, Ahmed A.; Othman, Sarah I.; Bin-Jumah, May; Al-Harbi, Hanan M.; Fouda, Moustafa M. G.
Abstract : New tricyanofuran intramolecular charge transfer dyes comprising the hydrazone group were prepared and fully characterized in order to study their possible solvatochromism, dyeing ability, and antimicrobial activity. The preparation of the hydrazone dyes was achieved in relatively good yields starting from different aromatic amines. The hydrazone functional group was presented via the azo-coupling reaction of the tricyanofuran compound by the properly substituted diazonium chloride. Chemical structures of the prepared hydrazones were confirmed via nuclear magnetic resonance spectroscopy ( 1 H- and 13 C-NMR), Fourier-transform infrared spectroscopy (FT-IR), and elemental analysis (C, H, and N). The UV-visible absorption spectra of the produced sensor colorants displayed interesting solvatochromism in solvents with a different polarity, which was found to be affected by the substituents bonded to the aromatic hydrazone moiety. The pH molecular switching was investigated through tuning the intramolecular charge transfer stimulated by the reversible deprotonation/protonation process in acetonitrile solution showing color change from yellow to purple. The produced disperse dyestuffs were employed for dyeing polyester fibers to introduce acceptable color strength and colorfastness properties. Moreover, the dyes verified a weak to moderate antimicrobial activity against some selected pathogens, including S. aureus, E. coli, and Candida albicans .